Al-Isykaliyyat al-Lughawiyyah fi Tarjamah Ma'ani al-Qur'an al-Karim ila al-Lughah al-Indonisiyyah - Saifullah Kamalie (TSAQAFAH, 2011)
Translating the Qur’an into Indonesian language, is a crucial issue, complicated and difficult. Because the Qur’an has a structure, pattern, and style of a particular language that can not be interpreted as translating Arabic books other. Although understand the Qur’an without going through the translation into Indonesian, is clearly more difficult. Recognizing the need for Qur’anic translation, the writer attempts to affirm the various aspects before translating to eliminate some errors, in terms of both language and content. From the translator qualifications he must understand well a few things; understand well the target and source language, semantics, and distinguish various linguistic structures such as synonyms, antonyms, and metaphor. According to Mildred L. Larsen, a translator must consider three aspects; a). differences in characteristics of language, b). sort out the confusion between the source language and its target, c). recognize the differences in the context of the uses of each word. Last but not least, the authors expect no results for translations of the Qur’an which maintained the validity – at least approached with the intention of the verses of the Qur’an – so it helps to understand the Qur’an properly. For that, the authors suggested, there needs to be a special team consisting of language experts and competent to translate the Qur’an in a collocation and groups.